The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/wej.12154
|View full text |Cite
|
Sign up to set email alerts
|

A septic tank‐UASB combined system for domestic wastewater treatment: a pilot test

Abstract: A 250 L and a 550 L pilot scale Up-Flow Anaerobic Sludge Blanket (UASB) reactors having different reactor height were fed septic tank effluents and operated at ambient temperatures of 08C to 308C. Both UASB reactors were fed intermittently at least 8 times per Hydraulic Retention Time (HRT) and the performance was monitored at 4d and 1d HRT. The removal efficiencies of Total Suspended Solid (TSS) and Total Chemical Oxygen Demand (COD t ) were about 59-68% and 54-59%, respectively, for both reactors at both HRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This hypothesis was corroborated by the observed decreased in the reactor's hydraulic performance and in methane degassing. Similar problems have been previously reported [28]; the same authors observed a COD accumulation of 25% (referred to COD influent load) and a COD conversion to methane of only 33%. Fig.…”
Section: Cod Loading Rate Cod Removal Efficiencies Effluent Concentsupporting
confidence: 87%
“…This hypothesis was corroborated by the observed decreased in the reactor's hydraulic performance and in methane degassing. Similar problems have been previously reported [28]; the same authors observed a COD accumulation of 25% (referred to COD influent load) and a COD conversion to methane of only 33%. Fig.…”
Section: Cod Loading Rate Cod Removal Efficiencies Effluent Concentsupporting
confidence: 87%
“…Since upflow anaerobic sludge blanket (UASB) reactors are widely applied in Brazil (Lohani et al . ), the wastewater treatment was analysed using this technology, followed by an anaerobic filter as an additional treatment step. The costs for implementation of the WWTPs were based on the analysis made by Pacheco () using several UASB + anaerobic filters which are installed in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the delayed degradation of organic waste in psychrophilic AD, it is suggested that the system should operate with a lower OLR and maintain a higher HRT than that of mesophilic AD. The OLR also has a significant effect on the performance of anaerobic digesters, and optimizing the HRT and OLR can lead to a more stable and efficient system with increased biogas production, even in psychrophilic AD [67]. A study found that at a low temperature of 10 • C and HRT of 20 d, there was an imbalance in the production of VFAs, with the concentration of propionate being almost three times that of acetate.…”
Section: Increasing Hrt and Lowering Olrmentioning
confidence: 99%